Efficacy of liraglutide in a patient with type 2 diabetes andcryptogenic cirrhosis - D'amico, E. (Acta Biomedica Atenei Parmensis, 2011)
In this work Author presents a case report of a female patient of 65 years old who had suffered from type 2 diabetes mellitus and from concomitant cryptogenic cirrhosis. She was treated with liraglutide, an analogue of human GLP-1, obtaining an optimal metabolic control associated with an improved clinical condition for the cirrhosis.